2004
DOI: 10.1080/02652030410001687681
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A in dried vine fruits on the Canadian retail market

Abstract: Between 1998 and 2000, 151 samples of raisins and sultanas and two samples of currants were collected from retail outlets across Canada and analysed for ochratoxin A. Samples were extracted with methanol-sodium bicarbonate, and the extracts were cleaned-up by immunoaffinity column chromatography. Ochratoxin A was quantified by liquid chromatography with fluorescence detection. The minimum quantifiable level was 0.1 ng (g-1). Ochratoxin A was present, above the minimum quantifiable level, in 67 (79%) of 85 samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 7 publications
6
27
1
Order By: Relevance
“…These findings are in agreement with some of previous studies in Argentina [24]. Although a lower occurrence rate was reported by Zinedin et al [20] (30%), and Imperato et al [25] high incidence rate of OTA in raising were more frequently observed in raisins analyzed in Germany [26], Sweden [27], Canada [28], Egypt [29] and Turkey [15,30]. Only one of the 15 dried apricot and two of the 20 dried date samples was contaminated with OTA at the 2.8 and 2.5 ng/g Level ( Table 2), which was below the maximum tolerance accepted by the European Commission (10 ng/g) [12].…”
Section: Resultssupporting
confidence: 80%
“…These findings are in agreement with some of previous studies in Argentina [24]. Although a lower occurrence rate was reported by Zinedin et al [20] (30%), and Imperato et al [25] high incidence rate of OTA in raising were more frequently observed in raisins analyzed in Germany [26], Sweden [27], Canada [28], Egypt [29] and Turkey [15,30]. Only one of the 15 dried apricot and two of the 20 dried date samples was contaminated with OTA at the 2.8 and 2.5 ng/g Level ( Table 2), which was below the maximum tolerance accepted by the European Commission (10 ng/g) [12].…”
Section: Resultssupporting
confidence: 80%
“…Sample sizes that have been chosen for analysis are 500 g (Mö ller and Nyberg 2003; Lombaert et al 2004), 1000 g (MacDonald et al 1999) and 3000 g (Meyvaci et al 2005). The heterogeneity of OTA in dried vine fruits is well illustrated by the study of Mö ller and Nyberg (2003), who prepared slurries of 150-275 g subsamples of raisins or currants in aqueous sodium bicarbonate.…”
Section: Mycotoxins In Dried Vine Fruitmentioning
confidence: 94%
“…Surveys for OTA have been carried out in many countries, including Argentina, Canada, the Czech Republic, Finland, France, Germany, Greece, Hungary, Sweden, the Netherlands, and the UK (Varga and Kozakiewicz 2006). Some maximum levels of OTA reported in the literature are 35 mg g À1 in raisins analysed in Sweden (Mö ller and Nyberg 2003), 250 mg kg À1 in raisins in Egypt (Youssef et al 2000), 26 mg kg À1 in sultanas analysed in Canada (Lombaert et al 2004), 54 mg kg À1 in unprocessed sultanas in Turkey (Meyvaci et al 2005), 100 mg kg À1 in processed Turkish sultanas (Aksoy et al 2007), and 54 mg kg À1 in currants analysed in the UK (MacDonald et al 1999). Taking some of the data from four of these surveys as examples: Lombaert et al (2004) found 79% of 85 samples of raisins and 59% of 66 samples of sultanas contained OTA above 0.1 mg kg À1 with overall mean levels in all samples of 1.8 mg kg À1 for both raisins and sultanas; Meyvaci et al (2005) covered three production years for unprocessed sultanas in the Aegean region of Turkey, finding considerable variations in incidence and median levels with an overall mean level 3.4 mg kg À1 ; while Aksoy et al (2007) reported varying incidences over five years in processed Turkish sultanas (with a overall mean concentration ¼ 1.4 mg kg À1 ).…”
Section: Mycotoxins In Dried Vine Fruitmentioning
confidence: 99%
“…Recent data from Canada reported that OTA was present in 79% of samples of raisins (Lombaert et al, 2004). OTA was present in 95% of dried fig samples from Brazil and 26% contained levels higher than 5 ng/g, and samples were infected particularly with A.…”
Section: Ota In Dried Fruitsmentioning
confidence: 99%